DEVELOPING COMMUNITY–BASED ECONOMY THROUGH CULTURAL CAPITAL DEVELOPMENT PROCESSES FOR SUSTAINABLE DEVELOPMENT - Wannako, Ruangurai; Kitkasachroen, Ekachai; Chantre , Napha; Sornkhaow, Sirimas (Journal of Graduate School Sakon Nakhon Rajabhat University, 2026)
The development of a community–based economy through cultural capital development processes for sustainable development was examined through document analysis and evaluated case studies. The development context focuses on strengthening the community economy by fostering economic, social, cultural and environmental relationships among community members to enhance cooperation, opportunities, and management systems. Emphasis is placed on preserving local wisdom by linking cultural foundations to generate income and circulate in the community resources within the community based on existing capital. The cultural capital development process comprises the following components: (1) access to production factors; (2) knowledge creation; (3) marketing; (4) communication to raise awareness; and (5) management in terms of cost control, accounting, and risk management. From the case studies of the cultural capital development processes for sustainable development, the Social Return on Investment (SROI) for the activity of cultural entrepreneur development was 2.489. The changes resulting from the development activity were as follows: "If cultural entrepreneurs are developed, there will be knowledge in the creative economy, cultural products that reflect significant cultural capital, and income distribution among cultural product entrepreneurs in the area".